Prácticas de literacidad en comunicación al realizar investigación cualitativa. - Zaragoza Peralta, Ana Gabriela; Montes Silva, Melanie Elizabeth (Enunciación)
The purpose of this work is to analyze the process followed by students of a Communication Sciences undergraduate program to elaborate a qualitative research report, which is why both read and produced texts, as well as professor guidance received by the students, were characterized for this analysis. The method used was focused ethnography, and the data were collected through class observations, interviews with the professor, and a student focus group. It was found that the activities designed by the professor were suitable for prompting the participation of the students in academic and disciplinary literacy practices. However, due to some faults in the provided guidance and accompaniment, the above was not always achieved, and the students participated in less sophisticated, uncritical, and reproductive practices. As a conclusion, this work stresses the importance that teachers explicitly teach students to participate in academic and disciplinary practices, so that they acquire the knowledge related to their field of study.